Pensando a guerra do Paraguai: representações simbólicas - Barroso, Giane Aparecida (2005)
This essay raises issues about studies elaborated by some scholars in Paraguay s war (1864 1870) from two symbological characters: Paraguay and Francisco Solano Lopez. The selected authors for this research treat Paraguay, since the period of colonization and/or from its independence (1811), and Solano Lopez, paraguayan president (1862 1870), with special focus, but with no similar perspectives; this enables to confront the different issues to notice the divergences, the convergences and the compliments. This way, there is an effort to dialogue with the other authors and make them dialogue among themselves so that the statute of the truth, pursued in the studies through the coherence and conviction of the arguments, can be emphasized and inquired. Therefore, the aim proposed in this work is to critically analyze the single image buildings, which allowed divergent configurations about Paraguay and Solano Lopez as important characters. This is one of the possible ways to think about the conflict in the middle of the 19th century and to understand some explaining arguments that turned out in a multiple and intriguing interpretation of the same historical fact: Paraguay s War.